Molecular and morphological phylogenetic analysis of Naupactus Dejean (Curculionidae: Entiminae) and Allied Genera: The dilemma of classification - del Rio, Maria Guadalupe (2018)
Naupactus (Curculionidae: Entiminae) is the most speciose weevil genus of the tribe Naupactini. The main objective of this work is to recognize species groups within Naupactus and to analyze the relationships between this and other Neotropical genera. For this purpose, we compiled a combined data matrix of 60 terminal units corresponding to 40 species for which we recorded 812 molecular and morphological characters (763 and 49 respectively), which were analyzed by Maximum Parsimony and Bayesian analyses. The single tree obtained from each analysis was rooted with Cyrtomon inhalatus. The species of Naupactus were recovered as different monophyletic groups, some of them closer to other genera of Naupactini (Lanterius, Teratopactus, Pantomorus and Parapantomorus) than to species of the same genus. We conclude that Naupactus is non-monophyletic, even though most species can be recognized based on a particular combination of morphological characters, which are probably symplesiomorphic. To be consistent with the cladistic principles, some genera diversified in marginal areas of the Pantomorus-Naupactus complex should be synonymized with Naupactus; however, these nomenclatural changes may not ensure a generic definition based on synapomorphies. We prefer to be conservative about the current classification until more evidence is available. The only nomenclatural amendments proposed herein are the transference of Naupactus inermis Hustache to Lanterius and of N. setarius to Symmathetes.